Origami Paper-Based Electrochemical Immunosensor with Carbon Nanohorns-Decorated Nanoporous Gold for Zearalenone Detection - Laza Correa, Anabel (2024)
Nowadays, mycotoxin contamination in cereals and wastewater exposes a safety hazard to consumer health. This work describes the design of a simple, low-cost, and sensitive origami microfluidic paper-based device using electrochemical detection for zearalenone determination. The microfluidic immunosensor was designed on a paper platform by a wax printing process. The graphitized carbon working electrode modified with carbon nanohorns-decorated nanoporous gold showed a higher surface area, sensitivity, and adequate analytical performance. Electrodes were characterized by scanning electron microscopy, energy-dispersive spectroscopy, and cyclic voltammetry. The determination of zearalenone was carried out through a competitive immunoassay using specific antibodies immobilized by a covalent bond on the electrode surface. In the presence of HRP-labeled enzyme conjugate, substrate, and catechol, zearalenone was detected employing the developed immunosensor by applying −0.1 V to the working electrode vs silver as a pseudo-reference electrode. A calibration curve with a linear range between 10 and 1000 µg Kg−1 (R2 = 0.998) was obtained, and the limit of detection and quantification for the electrochemical immunosensor were 4.40 and 14.90 µg Kg−1 , respectively. The coefficient of variation for intra- and inter-day assays was less than 5%. The selectivity and specificity of the sensor were evaluated, comparing the response against zearalenone metabolites and other mycotoxins that could affect the corn samples. Therefore, origami is a promising approach for paper-based electrochemical microfluidic sensors coupled to smartphones as a rapid and portable tool for in situ mycotoxins detection in real samples.